KOLONG DI ARSITEKTUR NUSANTARA - Ramdhani, Iga Nur; Prihatmaji, Yulianto P (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2021)
As an archipelago, Indonesia has diversity in archipelago architecture. In terms of diversity, Indonesia still has things that can unite the archipelago, one of which is the existence of kolong. Kolong is one of the characteristics of Nusantara Architecture. Kolong has different shapes, sizes and philosophies, and this diversity can be found in various regions throughout Indonesia. Kolong is the lower space of a building formed from the stilt structure of buildings in the archipelago. In its manifestation, kolong in the archipelago formed from various aspects, from the aspect of disaster response, climate response, humidity response, protection from wild animals and other tribes, to livestock, to emerging from the cosmological aspect. These aspects form a variety of kolong according to the nature and cultural elements of each region. The existence of kolong can be identified and mapping is carried out in this study. The diversity of kolong in Nusantara Architecture is mapped into five approaches, namely the state of the art, paradigms, concepts, technology, and models. Keywords: Nusantara architecture, Kolong, state of the art, paradigm, concept, technology, model ABSTRAK Sebagai negara kepulauan, Indonesia memiliki keberagaman dalam Arsitektur Nusantara. Dalam keberagaman, Indonesia tetap memikili hal yang dapat menyatukan Nusantara, salah satunya adalah keberadaan kolong. Kolong merupakan salah satu ciri khas dari Arsitektur Nusantara. Kolong memiliki bentuk, ukuran dan filosofi yang beragam, dan keragaman tersebut dapat dijumpai di berbagai daerah di seluruh Indonesia. Kolong merupakan ruang bawah dari suatu bangunan yang terbentuk dari struktur panggung pada bangunan-bangunan di Nusantara. Dalam perwujudannya, kolong di Nusantara terbentuk dari berbagai aspek, mulai dari segi tanggap bencana, tanggap iklim, tanggap kelembaban, perlindungan dari hewan buas dan suku lain, untuk berternak, hingga muncul dari aspek kosmologi. Aspek-aspek tersebut membentuk ragam kolong yang sesuai dengan alam dan unsur budaya masing-masing daerah. Hingga keberadaan kolong dapat diidentifikasi dan dilakukan pemetaan dalam penelitian ini. Keberagaman kolong di Arsitektur Nusantara dipetakan dalam lima pendekatan, yaitu state of the art, paradigma, konsep, teknologi, dan model. Kata kunci: Arsitektur Nusantara, Kolong, state of the art, paradigma, konsep, teknologi, model